2023
DOI: 10.3390/pediatric15030041
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Diaphragmatic Eventration in the Neonatal Period: Systematic Review of the Literature and Report of a Rare Case Presenting with Gastrointestinal Disorders

Aikaterini Konstantinidi,
Paraskevi Liakou,
Paschalia Kopanou Taliaka
et al.

Abstract: Background: The term congenital diaphragmatic eventration (CDE) refers to an anatomical abnormality of the diaphragm. It is a very rare condition; however, early and prompt diagnosis is of very great importance due to possible life-threatening complications. Most severely affected patients are neonates, usually presented with respiratory distress symptoms. The aim of this study was to systematically review the existing literature and to consolidate data on CDE in neonates as well as to report a case of a neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Thus, according to the owner’s opinion, conservative management with periodic monitoring was selected to evaluate the severity of the protrusion and clinical signs. In humans, a study reviewing 109 cases revealed that the recurrence rate after surgical intervention for true DE was 8.3% [ 14 ]. Repair of DE by mesh is known in human medicine, and the mesh can be implanted to maintain the tone of the diaphragm when the overall diaphragm is too lax to maintain tone.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, according to the owner’s opinion, conservative management with periodic monitoring was selected to evaluate the severity of the protrusion and clinical signs. In humans, a study reviewing 109 cases revealed that the recurrence rate after surgical intervention for true DE was 8.3% [ 14 ]. Repair of DE by mesh is known in human medicine, and the mesh can be implanted to maintain the tone of the diaphragm when the overall diaphragm is too lax to maintain tone.…”
Section: Discussionmentioning
confidence: 99%